The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fmicb.2017.00128
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Prediction of Two M. tuberculosis Clinical Isolates Reveals Their High Antigenic Density and Potential Drug Targets

Abstract: The Excreted/Secreted (ES) proteins play important roles during Mycobacterium tuberculosis invasion, virulence, and survival inside the host and they are a major source of immunogenic proteins. However, the molecular complexity of the bacillus cell wall has made difficult the experimental isolation of the total bacterial ES proteins. Here, we reported the genomes of two Beijing genotype M. tuberculosis clinical isolates obtained from patients from Vietnam (isolate 46) and South Africa (isolate 48). We develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 54 publications
4
34
4
Order By: Relevance
“…Furthermore, the average AAR of the secretome and cell membrane proteins was also found to be significantly lower (p < 0.001) and significantly higher (p < 0.001), respectively, in comparison to the average AAR of randomly chosen, equally sized sets of proteins from the whole proteome (Methods). Note that similar observations on relative AAR of secretome and cell membrane proteins were also recently made in tapeworms, Taenia solium 24 and Echinococcus multilocularis 92 , and in bacterium Mycobacterium tuberculosis 93 . Thus, secreted proteins are likely to be more antigenic than cell membrane proteins, and while choosing candidates for vaccine development, the secretome may provide a more antigenic landscape than cell membrane proteins.…”
Section: Antigenicity Of the Secretomesupporting
confidence: 78%
“…Furthermore, the average AAR of the secretome and cell membrane proteins was also found to be significantly lower (p < 0.001) and significantly higher (p < 0.001), respectively, in comparison to the average AAR of randomly chosen, equally sized sets of proteins from the whole proteome (Methods). Note that similar observations on relative AAR of secretome and cell membrane proteins were also recently made in tapeworms, Taenia solium 24 and Echinococcus multilocularis 92 , and in bacterium Mycobacterium tuberculosis 93 . Thus, secreted proteins are likely to be more antigenic than cell membrane proteins, and while choosing candidates for vaccine development, the secretome may provide a more antigenic landscape than cell membrane proteins.…”
Section: Antigenicity Of the Secretomesupporting
confidence: 78%
“…Additionally, the abundance of antigenic regions (AAR), which evaluates antigenic density, found differences that were statistically significant between the NW and the O groups. As previous studies by our group have shown, the secretomes of more virulent pathogenic bacteria tend to have a higher antigenic density; this may be an indicator of pathogen activity in the obese subjects that may deserve further study [15,51].…”
Section: Discussionmentioning
confidence: 65%
“…Proteins can be secreted by bacteria through multiple secretory mechanisms. Thus, we used a bioinformatic strategy [14,15] to predict the secreted proteins encoded in our metatranscriptome. Out of the 115,712 genes that codify for proteins, we predicted 30,024 as potentially secreted, which represented ~ 26% of the total proteins in our metatranscriptome.…”
Section: Determination Of the Secrebiomementioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial secretomes have been studied by different approaches including in silico identification of secretion signals, isolation of the secretomes of in vitro cultured microorganisms under different growth conditions and screening of proteins by phage display. In silico based approaches rely on algorithms to find consensus secretion signals characteristic of secreted proteins [ 95 ]. Secreted proteins are usually targeted to the secretory pathway by a signal either encoded in the N-terminal region of the protein or by the 5′ end of the mRNA sequence [ 96 ].…”
Section: Secretomics For Identifying Bacterial Extracellular Effecmentioning
confidence: 99%